Answer:
4.) ![y=-1](https://tex.z-dn.net/?f=y%3D-1)
5.) ![y=-1x+4](https://tex.z-dn.net/?f=y%3D-1x%2B4)
Step-by-step explanation:
Use the slope-intercept form for each:
![y=mx+b\\\\m=slope\\\\b=y-intercept\\\\(x,y)](https://tex.z-dn.net/?f=y%3Dmx%2Bb%5C%5C%5C%5Cm%3Dslope%5C%5C%5C%5Cb%3Dy-intercept%5C%5C%5C%5C%28x%2Cy%29)
The y-intercept happens when x is equal to zero, so when you have the point (0,y), plug in the y-value as the y-intercept.
4.) Insert the appropriate values in the equation:
![y=0x-1](https://tex.z-dn.net/?f=y%3D0x-1)
Simplify. Any number multiplied by 0 is 0, so:
![y=0+-1\\\\y=-1](https://tex.z-dn.net/?f=y%3D0%2B-1%5C%5C%5C%5Cy%3D-1)
5.) Insert the appropriate values:
![y=-1x+4](https://tex.z-dn.net/?f=y%3D-1x%2B4)
This cannot be simplified further.
:Done